Rodent islet amyloid polypeptide (IAPP) selectively enhances GABAA receptor-mediated neuronal inhibition in mouse ventral but not dorsal hippocampal dentate gyrus granule cells - Olga Netsyk; Sergiy V. Korol; Gunilla T. Westermark; Bryndis Birnir; Zhe Jin (Frontiers in Cellular Neuroscience)
Islet amyloid polypeptide (IAPP, amylin) is a peptide hormone that plays an important role in glucose homeostasis but has been implicated in the pathophysiology of type 2 diabetes and Alzheimer’s disease. However, its effect on neurotransmission in the hippocampus remains poorly understood. Here, we investigated the impact of non-amyloidogenic rodent IAPP (rIAPP) on GABAA receptor-mediated neuronal inhibition in mouse dorsal and ventral hippocampal dentate gyrus (DG) granule cells. Using whole-cell patch-clamp recordings, we showed that rIAPP selectively enhanced both GABA-activated spontaneous and miniature inhibitory postsynaptic currents (sIPSCs and mIPSCs) in ventral, but not dorsal, hippocampal DG granule cells. The effect of rIAPP on sIPSCs was completely abolished in the presence of the amylin receptor antagonist IAPP8–37. Interestingly, GABAA receptor-mediated tonic current density remained unchanged in either dorsal or ventral hippocampal DG granule cells during rIAPP application. This region-specific and inhibition type-specific effect of rIAPP is likely associated with differential modulation of presynaptic GABA release as well as postsynaptic GABAA receptors in the ventral as compared to the dorsal hippocampus. Our results suggest that rodent IAPP acts as a neuromodulator in hippocampal subregions by altering the strength of GABAA receptor-mediated inhibitory signaling.